KAPABILITAS SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PENYAKIT MASYARAKAT DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2022-2023 - Pertiwi, Sukma; ,, Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the capability of the Civil Service Police Unit (Satpol PP) of Kuantan Singingi Regency in controlling social illnesses in Kuantan Tengah District during 2022–2023. According to Regional Regulation of Kuantan Singingi Regency Number 14 of 2010, which amends Regional Regulation Number 20 of 2002 on Social Illnesses, individuals involved in social illness activities should be subject to criminal sanctions or fines. However, in practice, Satpol PP only applied non-penal measures, such as verbal warnings, the signing of written statements, and the confiscation of evidence. This research is important to evaluate the effectiveness of enforcement actions and to analyze the need for strengthening the capability of Satpol PP in upholding regional regulations. This research was conducted using a qualitative approach and descriptive analysis. The types of data used are primary and secondary data. Primary data were obtained through interviews with informants, while secondary data consisted of supporting information gathered from relevant documents. Data collection techniques included interviews and documentation. The research findings indicate that controlling social illnesses in Kuantan Tengah District, Kuantan Singingi Regency, requires collaboration involving the Civil Service Police Unit (Satpol PP), Traditional Institutions, and the local community. The capability of Satpol PP of Kuantan Singingi Regency needs to be strengthened by understanding local wisdom and social norms. The success of law enforcement heavily depends on social support, inter-agency coordination, and strategies that are humanistic and based on local cultural values. Keywords: Capability, Social Illness , Local Wisdom